Konstruksi Model Tata Kelola Kolaboratif Pendidikan Islam Berbasis Pesantren dalam Pengembangan Masyarakat Pedesaan - Anita Anita; Shohib Hasan; Poniah Poniah (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
The development of Islamic education in rural communities requires a governance model capable of integrating educational institutions, pesantren, local communities, and village government within a sustainable collaborative framework. This study aims to construct a collaborative governance model of pesantren-based Islamic education in rural community development. The research employed a qualitative approach using grounded theory and was conducted in Sidoharjo Village, Jati Agung District, South Lampung Regency. Data were collected through in-depth interviews, participant observation, documentation, and focus group discussions involving pesantren leaders, school principals, village government officials, religious leaders, community leaders, alumni, and parents. Data analysis was carried out through open coding, axial coding, and selective coding to generate a conceptual model grounded in empirical findings. The findings reveal that the development of Islamic education in Sidoharjo Village is supported by a collaborative relationship among pesantren, formal educational institutions, local communities, village government, and alumni. This collaboration is strengthened by pesantren values, social trust, community participation, religious commitment, and institutional support, which collectively contribute to the enhancement of educational awareness, religious consciousness, social participation, and community development. The study further identifies a collaborative governance model consisting of four interconnected dimensions: pesantren values, stakeholder collaboration, educational empowerment, and rural community transformation. The model demonstrates that sustainable Islamic education development can be achieved through collective engagement and shared responsibility among stakeholders. Consequently, the proposed model contributes to the advancement of Islamic Educational Management by providing a conceptual and practical framework for strengthening pesantren-based educational governance in rural communities.